2001
DOI: 10.1068/p3127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voluntary Attention on Structured Afterimages

Abstract: The effect of voluntary attention on afterimage fragmentation was explored in two experiments. The afterimage, in the form of a 30 degrees-tilted star of David, was generated after prolonged steady fixation in the first experiment, and with a brief and intense flash in the second experiment. Subjects were instructed to select various target shapes in the afterimage for attention and, at the same time, observe what was visible or invisible. Verbal reports and manual responses to afterimage changes were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
(16 reference statements)
1
22
0
Order By: Relevance
“…Similarly, attentional withdrawal decreases the size of the aftereffect for real (16,(28)(29)(30) and illusory lines (31), and for motion (32)(33)(34)(35)(36) and face (22) aftereffects. Curiously, though, attentional withdrawal seems to increase the duration of afterimages induced by real (37)(38)(39)(40) and illusory adaptors (41). These latter findings beg the question: Could attention and consciousness affect perception in different and experimentally separable ways, even though up to now they have been found to work synergistically (4,42)?…”
mentioning
confidence: 88%
“…Similarly, attentional withdrawal decreases the size of the aftereffect for real (16,(28)(29)(30) and illusory lines (31), and for motion (32)(33)(34)(35)(36) and face (22) aftereffects. Curiously, though, attentional withdrawal seems to increase the duration of afterimages induced by real (37)(38)(39)(40) and illusory adaptors (41). These latter findings beg the question: Could attention and consciousness affect perception in different and experimentally separable ways, even though up to now they have been found to work synergistically (4,42)?…”
mentioning
confidence: 88%
“…The fifth argument derives from the experiments showing that in some specific conditions attention has an adverse effect on conscious experiences (Lou, 2001; Tsuchiya and Koch, 2009; Rahnev et al, 2011). Voluntary covert attention to color afterimage, afterimage of spatially modulated contrast, or spatially localized motion aftereffect tends to speed up their decay from awareness (Lou, 2001; Suzuki and Grabowecki, 2003; Wede and Francis, 2007; Bachmann and Murd, 2010; van Boxtel et al, 2010a; Murd and Bachmann, 2011).…”
Section: Why It Can Be Said That Attention Is Not the Basis For Conscmentioning
confidence: 99%
“…Voluntary covert attention to color afterimage, afterimage of spatially modulated contrast, or spatially localized motion aftereffect tends to speed up their decay from awareness (Lou, 2001; Suzuki and Grabowecki, 2003; Wede and Francis, 2007; Bachmann and Murd, 2010; van Boxtel et al, 2010a; Murd and Bachmann, 2011). Sixth, some aspects of a scene such as the gist or animated objects can be explicitly noticed without attention and without compromising the competing focused attention task (van Boxtel et al, 2010b; see, however, Cohen et al, 2011).…”
Section: Why It Can Be Said That Attention Is Not the Basis For Conscmentioning
confidence: 99%
“…For example, it has been found that AI of a pattern becomes weaker when the pattern is attended345. Moreover, the perceived size of the inducing stimulus determines the size of the AI6.…”
mentioning
confidence: 99%